Compare the Quality of Root Canal Obturation by Intraoral Periapical Radiographs in Single Rooted Teeth Prepared by Manual Technique Versus Rotary Method (Medical Forum Monthly, 2021)
Objective: To compare the quality of root canal obturation by intraoral periapical radiographs in single rooted teeth prepared by manual technique versus rotary method.Study Design: Randomized controlled trial study. Place and Duration of Study: This study was conducted at the Study was conducted at Punjab Dental Hospital, Lahore for six months duration from July to December, 2020.Materials and Methods: Hundred teeth of male and female patients with ages 20 to 65 years were enrolled and divided equally into two groups. Group I consist of 50 teeth and rotary method was applied. Group II with 50 teeth and manual instrumentation was done. Post obturation radiographs were done to examine the difference in length, density and taper of root canal filling by using T-score.Results: There were 64 (64%)females and 36 (36%) male patient’s teeth with mean age 33.52±10.86 years. We found a significant difference in term of obturation quality between both groups with p-value 0.008. In group I 19 (38%) patients had T-score 2 and 24 (48%) had T-score 3 while in group II 17 (34%) patients had T-score 2 and 11 (22%) patients had T-score 3, a significant difference was observed between both techniques with p-value <0.05.Conclusion: Compared to manual approach, the root system in terms of root canal shutting consistency was higher.